FEATURES OF BLOOD GAS COMPOSITION AND ACID-BASE BALANCE IN CHILDREN WITH ACUTE RESPIRATORY FAILURE CAUSED BY THE NEW CORONAVIRUS SARS-CoV-2 - Teslіtskyi, O.K.; Koloskova, O.K.; Tarnavska, S.I.; Romanchuk, L.I. (World of Medicine and Biology, 2024)
A comprehensive examination of 61 children with severe acute respiratory infections made it possible to establish that in patients with a coronavirus infection caused by SARS-CoV2, upon admission to the Department of Anesthesiology and Intensive Care, more pronounced hypoxemia was probably registered more often. It was reflected statistically significant risks of SpO2 reduction30 mmol/l (odds ratio – 3.4).
Keywords: respiratory failure; COVID-19; children; blood gas composition